Magnetic position sensor system for alignment detection of pipelines - Jung, Seyoon; Kim, Sihyeok; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2021)
When a pipeline is inserted into the joint coupler, frequent fires and uneven fusion occur in a trial of fusion without reaching to a desired position. To solve the matters, a positioning sensor and sensor system were developed that provide the information of electrical signal to PC whether the cut surface of the pipeline has reached the correct position. The developed sensor system consists of two permanent magnetic tapes, two magnetic hall sensors, and a PC. As the magnetic tape and sensor were aligned in the center to center, a large magnetic strength was observed from the sensor. A large change in sensor signal was also observed as the aligned center was laterally misplaced. By comparing the values of the two sensors, a vertical alignment status of the pipeline was affirmed which provides whether the pipeline was located in the center inside the cylindrical joint coupler. Overall system performances were evaluated in terms of the length, width, thickness of the magnetic tape, and ambient temperature change. The output signal of the sensor was finally analyzed as an electric signal instead of magnetic strength that was transmitted to PC to determine whether the fusion process should begin.
Keywords: Ambient temperature change; Cylindrical joints; Electrical signal; Magnetic Hall sensors; Magnetic position sensors; Magnetic strength; Permanent magnetics; Vertical alignment; Joint coupler; Magnetic sensor; Magnetic tape; PE fusion; PE pipeline; Positioning sensor